Regulation of IL-10 production in dendritic cells is controlled by the co-activation of TLR2 and Mincle by Lactiplantibacillus plantarum OLL2712 - Ryuhei Sakabe; Kazumasa Onishi; Junko Mochizuki; Takayuki Toshimitsu; Tomoyuki Shimazu; Shigenobu Kishino; Jun Ogawa; Sho Yamasaki; Toshihiro Sashihara (Microbiology Spectrum)
ABSTRACT We showed that Lactiplantibacillus plantarum OLL2712 (OLL2712) strongly induces interleukin (IL)-10 production in immune cells. Although beneficial effects of this strain have been observed in both mice and humans, the mechanisms underlying IL-10 induction remain unclear. In this study, we found that OLL2712 co-activates two pattern recognition receptors, leading to IL-10 production in the mouse-derived thermosensitive dendritic cell line, tsDC. We first revealed the involvement of the Toll-like receptor (TLR)2-Myeloid differentiation primary response gene (MYD) 88 pathway in OLL2712-induced IL-10 production in tsDCs. However, stimulation with the TLR2 agonist alone was insufficient to induce IL-10 production. Consequently, we explored additional signaling pathways and found that the phosphorylation of spleen tyrosine kinase (Syk) was important in response to OLL2712, which was not triggered by a TLR2 agonist alone. Notably, the activation of Syk was found to depend on macrophage-inducible C-type lectin receptor (Mincle), one of the C-type lectin receptors. However, the surface-expressed Mincle is not responsible for the IL-10 production by OLL2712. Instead, it depends on the incorporation of OLL2712 into tsDCs, suggesting that Mincle recognizes incorporated OLL2712 intracellularly. In summary, OLL2712 is initially recognized by TLR2, which subsequently induces the expression of Mincle to recognize incorporated OLL2712, ultimately inducing IL-10 production.IMPORTANCEThe objective of this study is to elucidate the mechanism by which Lactiplantibacillus plantarum OLL2712 (OLL2712), previously identified by our research group as a potent stimulator of interleukin-10 production in immune cells, exerts its immunomodulatory effects. Our findings indicate that OLL2712 acts in synergy with two pattern-recognition receptors: Toll-like receptor 2 and Macrophage inducible C-type lectin receptor (Mincle). Additionally, we observed that OLL2712 needs to be internalized intracellularly to be recognized by Mincle. These findings represent the first insights into the detailed mechanism underlying the anti-inflammatory effects of OLL2712.